The Effectiveness of Cognitive Processing Therapy on Cognitive Regulation of Emotion and Personal Growth of Children of Shahed and Isargar Families - Namjo, Farhad; Sajjadian , Ilnaz; Golparvar , Mohsen (Applied Family Therapy Journal (AFTJ), 2020)
Aim: This study aimed to determine the effectiveness of cognitive processing therapy on cognitive regulation of emotion and personal growth of children of Shahed and Isargar families. Method: The present study was quasi-experimental with experimental and control groups and pretest-posttest design with one-month follow-up. The statistical population of this study was 135 children of Shahed and Isargar families of Shahed Secondary School and Yasouj University. After screening using the Cognitive Emotion Regulation questionnaire of Garnefski et al (2002) and Robitsckek,s Personal Growth(1998), 30 people were selected and in the experimental group of cognitive processing (n = 15) and the control group (n = 15) were randomly replaced. The experimental group underwent 12 sessions of 90-minute cognitive processing intervention by Ressick, Nishis, Weaver, Austin, and Fauer (2007); Then both groups were evaluated in three stages of pre-test, post-test, and follow-up by cognitive emotion regulation questionnaires and personal growth. Data were analyzed using repeated measures mixed variance analysis. Results: The results showed the effect of cognitive processing therapy on the emotional regulation of adaptive strategy (P=0.015, F = 6.70), emotion regulation of non-adaptive strategy (P=0.001, F = 15.71), and individual growth intervention (p=0.031, F = 5.14) in the post-test stage and the stability of this effect was in the follow-up stage. Conclusion: Since cognitive processing, therapy promotes emotional regulation of personal growth; therefore, it can be used to improve the cognitive regulation of emotion and personal growth in children of Shahed and Isargar families.